2021
DOI: 10.1016/j.bbrep.2021.100911
|View full text |Cite
|
Sign up to set email alerts
|

Influence of pentoxifylline on gene expression of PAG1/ miR-1206/ SNHG14 in ischemic heart disease

Abstract: The regulation by immune checkpoint is able to prevent excessive tissue damage caused by ischemia reperfusion (I/R); therefore, the study aims to investigate the behavior of phosphoprotein associated with glycosphingolipid-enriched microdomains 1 (PAG1) mRNA, miR-1206 and small nucleolar RNA host gene 14 (SNHG14) during I/R and intake of pentoxifylline (PTX) as a protective drug. The relative expression level of PAG1/miR-1206/SNHG14 was determined by qRT-PCR. Cardiac tissue levels of cytotoxic T-lymphocyte ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…It was found that could be used as the biomarker for ischemia reperfusion diagnosis. 24 MiR‐1206 variant was confirmed to be related to methotrexate‐induced oral mucositis in childhood acute lymphoblastic leukemia. 25 In cancer, Yu et al 26 showed that circ_0092367 suppressed epithelial‐mesenchymal transition process and gemcitabine resistance via miR‐1206 in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 94%
See 1 more Smart Citation
“…It was found that could be used as the biomarker for ischemia reperfusion diagnosis. 24 MiR‐1206 variant was confirmed to be related to methotrexate‐induced oral mucositis in childhood acute lymphoblastic leukemia. 25 In cancer, Yu et al 26 showed that circ_0092367 suppressed epithelial‐mesenchymal transition process and gemcitabine resistance via miR‐1206 in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 94%
“…MiR‐1206 is a functional miRNA. It was found that could be used as the biomarker for ischemia reperfusion diagnosis 24 . MiR‐1206 variant was confirmed to be related to methotrexate‐induced oral mucositis in childhood acute lymphoblastic leukemia 25 .…”
Section: Discussionmentioning
confidence: 98%
“…In osteosarcoma, miR-593-3p can inhibit tumorigenesis by promoting the upregulation of zinc finger E-box binding homeobox 2( 50 ). SNHG14( 51 ) and MAP3K2( 52 ) genes have been shown to serve as targets of miR-1206 and miR-1208 respectively, and miR-1206 and miR-1208 can act as targets for tumor suppression.…”
Section: Discussionmentioning
confidence: 99%
“…Therapeutic intervention targeting PAG could take the form of an inhibitory antibody or a compound to change expression level. The anti-inflammatory/vasodilatory drug pentoxifylline has been shown to decrease PAG expression levels in T cells ( 169 ). Because PAG is a transmembrane protein, it can be targeted by the same approach used in traditional immunotherapy – development of an antibody to bind and inhibit signaling.…”
Section: Pagmentioning
confidence: 99%